The impact of macroeconomic policies on the growth of public health expenditure: An empirical assessment from the Indian states - Deepak Kumar Behera; Umakant Dash (Cogent Economics & Finance, 2018)
The impact assessment of macroeconomic policies on public health expenditure is very relevant in Indian economy because of tax reform, fiscal consoli- dation, and expenditure policy reform. These have been undertaken after economic liberalization in order to sustain a high economic growth. Despite the several fis- cal policy initiatives, there is a persistent slowing down of growth in public health expenditure and a huge disparity in the allocation of budget toward health care among the Indian states. Using the period 1990-2014, the study examines the dynamic relationships between public health expenditure and macroeconomic fac- tors (economic growth, domestic revenue, domestic debt, fiscal balance, and central government transfer) of 15 major states of India. Our empirical result shows that state's revenue (i.e. tax revenue and indirect tax) and central transfer (i.e. tax devo- lution) are the major public providers for financing the health care of Indian states. Other sources of revenue of the government, namely non-tax revenue and direct tax show no impact on public health expenditure in the short run, while it shows a positive impact in the long run. As a consequence, we find that economic growth and fiscal balance lead to a favorable impact on public health expenditure in the long run. The result suggests the improvement in revenue collection, increase in the tax base and the efficient utilization of central grants would generate fiscal space in the economy, and thereby the government can allocate more funds toward public health care.
Keywords: 330; public health expenditure; economic growth; fiscal space; tax revenue; fiscal balance; domestic debt; central grants; economic liberalization; Indian states; Indian economy